2014
DOI: 10.1371/journal.pone.0097632
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Endoglin, Transforming Growth Factor-Beta 1 and Soluble Tumor Necrosis Factor Alpha Receptors in Different Clinical Manifestations of Preeclampsia

Abstract: BackgroundDespite intensive research, the etiopathogenesis of preeclampsia (PE) remains uncertain. Inflammatory and angiogenic factors are thought to play considerable roles in this disease. The objective of this study was to investigate the association between soluble endoglin (sEng), transforming growth factor beta-1 (TGF-β1) and tumor necrosis factor alpha soluble receptors (sTNF-Rs) and the clinical manifestations of PE.MethodsPlasma levels of sEng, TGF-β1 and sTNF-Rs were determined by ELISA in 23 non-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 52 publications
2
44
0
Order By: Relevance
“…lated, while anti-inflammatory cytokine IL-10 was downregulated in PE 22,27,28. The pro-inflammatory lipid mediator LTB4 was increased in the plasma of PE women compared with normotensive pregnant women in the current study.…”
supporting
confidence: 41%
See 1 more Smart Citation
“…lated, while anti-inflammatory cytokine IL-10 was downregulated in PE 22,27,28. The pro-inflammatory lipid mediator LTB4 was increased in the plasma of PE women compared with normotensive pregnant women in the current study.…”
supporting
confidence: 41%
“…17,18 In this sense, it is widely accepted that normotensive pregnancy is physiologically associated with a higher pro-inflammatory status when compared to the non-pregnant state. 21,22 LTB4 is a lipid mediator endowed with pro-inflammatory activities. 21,22 LTB4 is a lipid mediator endowed with pro-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…While the data regarding levels of circulating TGF-β during PE is not consistent, some studies have shown the cytokine to be increased during PE (4951). Since activated platelets occur in some women with PE and are known to produce TGF-β, this would explain why some researchers see an increase in TGF-β during the disease (51).…”
Section: Discussionmentioning
confidence: 98%
“…Since activated platelets occur in some women with PE and are known to produce TGF-β, this would explain why some researchers see an increase in TGF-β during the disease (51). This could be an explanation for the increase in TGF-β seen in the RUPP rats; however, platelets were not examined in this study, or have they been shown to be increased by others.…”
Section: Discussionmentioning
confidence: 99%
“…It can also significantly affect the fetoplacental unit, causing intrauterine growth restriction and premature birth [3,6,7]. Although the pathophysiologic mechanisms underlying this disease have not yet been fully elucidated, there is evidence that a high level of antiangiogenic molecules, for example, soluble fms-like tyrosine kinase 1 (sFlt-1) and soluble endoglin (sEng), in the maternal circulation, is associated with this pregnancy complication [8][9][10][11][12].…”
mentioning
confidence: 99%